Consumer attitudes towards ultrasound processing and product price: Guava juice as a case study (Scientia Agropecuaria, 2021)
Several kinds of emerging technology have begun to be applied to food processes as prospective alternatives to conventional methods.  Among these, ultrasound has been used. Despite the vast literature on the subject, some important aspects, including the sensory and hedonic perception of consumers towards this technology have not been properly addressed. In this study, consumer attitudes toward expected acceptance, pricing and purchase intention of guava juice processed with ultrasound technology were analyzed by using the conjoint analysis. The holistic perception of guava juice using projective mapping was also evaluated. The results indicate that consumers have greater acceptance and purchase intention for products that inform them of the benefits of the ultrasound process, while purchase intention was mainly influenced by the lowest price. Moreover, the product information regarding the ultrasound technology -displayed on individual packages- was a predominant factor which also served as a criterion for grouping the stimuli. Overall, the information highlighting the use of ultrasound technology during the processing of guava juice did not have any negative effect on the consumers’ acceptance and purchase intention. These findings can be considered as a positive indicator towards the possible application of this technology to industrial juice processing.
Keywords: ultrasound technology; food processing; conjoint analysis; projective mapping; expected acceptance; purchase intention